Novel Nomograms to Predict Delayed Hyponatremia After Transsphenoidal Surgery for Pituitary Adenoma - Lin, Kunzhe; Zeng, Ran; Mu, Shuwen; Lin, Yinghong; Wang, Shousen (Frontiers in Endocrinology, 2022)
Objective: This study aimed to develop a nomogram of clinical variables and magnetic resonance imaging scans to predict delayed hyponatremia after transsphenoidal surgery for pituitary adenoma. Methods: Patients who underwent transsphenoidal surgery for pituitary adenoma in Fuzong Clinical Medical College of Fujian Medical University between January 2012 and December 2020 were retrospectively investigated. Medical records, MRI findings, and laboratory examination results were recorded as candidate variable predictors of delayed hyponatremia. A nomogram to predict delayed hyponatremia was formulated based on the multivariable model of risk factors. The predictive accuracy and discriminative ability of the nomogram were assessed using the receiver operating characteristic (ROC) curve, calibration plot, and decision curve analyses. The model underwent prospective validation in three medical centers with patients who underwent transsphenoidal surgery for pituitary adenoma between January 2021 and February 2022. Results: The model that incorporated the postoperative length of “measurable pituitary stalk,” pituitary stalk deviation angle difference, postoperative diabetes insipidus, sinking depth of diaphragma sellae, and blood sodium level on the second postoperative day was developed and presented as the nomogram of the training cohort. The nomogram achieved area under the ROC curve (AUCs) of 0.806 and 0.849 for the training cohort and the testing cohort, respectively, and displayed good calibration. Decision curve analysis showed that the nomogram was clinically useful when the threshold probability was 13–96%. Conclusions: We developed a nomogram to evaluate the individualized prediction of delayed hyponatremia after transsphenoidal surgery for pituitary adenomas.